KEPATUHAN TENAGA KESEHATAN TERHADAP KODE ETIK PROFESI: ANALISIS LITERATUR UNDANG-UNDANG DAN PRAKTEK DI LAPANGAN - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Health workers' compliance with professional codes of ethics is a key element in ensuring quality health services, protecting patients' rights, and maintaining professional integrity. This study aims to analyse health workers' compliance with professional codes of ethics based on a review of legislation and practices in the field. The method used is a qualitative literature review, examining regulations such as the Health Law, Hospital Law, and professional codes of ethics from health professional organisations. The results of the analysis indicate that healthcare workers' compliance is influenced by various factors, including education and training, organisational culture, sanction and reward systems, work pressure, personal ethical values, and social norms and community expectations. Although regulations and codes of ethics have been comprehensively formulated, their implementation in the field still faces challenges such as weak coordination between institutions, lack of understanding of laws and ethics among health workers, and inadequate enforcement mechanisms. This study recommends the need to strengthen ethical education, harmonise regulations, and enhance supervision and disciplinary enforcement to ensure consistent compliance with professional ethical codes, thereby improving the quality of healthcare services and public trust.